The Influence of Internal Corporate and Macroeconomic Factors on Stock Prices - Bulan Oktrima; Abdillah Akbar Alhasby (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the influence of internal corporate factors and macroeconomic variables on stock prices of property and real estate companies listed on the Indonesia Stock Exchange during the 2015–2024 period. The independent variables include capital structure, profitability, company size, price to book value, inflation, and the rupiah exchange rate, while stock price is used as the dependent variable. This research applies a quantitative approach using secondary data obtained from company financial statements and official publications. The data were analyzed using panel data regression with the Random Effects Model (REM), supported by classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that profitability, company size, price to book value, and the rupiah exchange rate have a significant effect on stock prices. Meanwhile, capital structure and inflation do not show a significant influence. Simultaneously, all independent variables significantly affect stock prices, as indicated by a Prob (F-statistic) value of 0.0000. The coefficient of determination (Adjusted R²) of 0.8673 shows that 86.73% of stock price variation can be explained by the variables used in this study, while the remaining 13.27% is influenced by other factors not included in the model. These findings suggest that company fundamentals and selected macroeconomic variables play an important role in determining stock price movements and can be considered by investors in making investment decisions.